Determination of Critical Indoor Air Quality Parameters in Environmental Chemistry Laboratory of President University - Gabryella Lovia Sihombing; Yosef Barita Sar Manik (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The Environmental Engineering Laboratory at President University is obliged to systematically identify and manage Environmental Health and Safety (EHS) aspects to comply with LAM Engineering Regulation No. 1 of 2025, which mandates Higher Education Institutions in Engineering to ensure the provision of appropriate laboratory infrastructure and continuous monitoring of EHS conditions within their facilities. Through a systematic identification process that aligns activities and working conditions with relevant regulations, 9 critical parameters have been established, including temperature, humidity, CO2, PM2.5, PM10, lighting, noise, airflow, and Total Suspended Particles (TSP). These findings were obtained based on the identification of potential pollution risks based on laboratory experiments based on study program modules, measurements of dimensions and equipment as well as indoor air circulation conditions and literature review on indoor air quality study and regulation. The results of the critical parameter determination provide a comprehensive picture of critical indoor air quality parameters in laboratories, thus forming the basis for the development of an appropriate EHS management system at President University laboratories. Based on these research results, it is recommended to regularly monitoring indoor air quality with monitoring device, move the furnace as source of particulates, and maintaining humidity by installing a dehumidifier to ensure a healthy and standard-compliant learning environment.